Analisis Frekuensi Langkah dalam Lari 100 Meter pada Atlet PASI Kabupaten Soppeng - Rizaldi, Ryan; Fajar, Abd. Malik; S, Nurishla; Hidayatullah, Muh Syarif; Saputra, Muh. Ilham; Farhan, Andi Muh Zuhri; Juhanis; Arfanda, Poppy Elisano (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the quality of stride frequency and 100-metre running speed among PASI athletes in Soppeng Regency. The study employed a quantitative approach using a descriptive method. The study population consisted of 25 PASI athletes from Soppeng Regency, with a sample of 15 athletes selected as research subjects. Data collection was carried out through a 100-metre sprint test and an observation sheet to measure stride frequency. The data obtained were analysed using descriptive statistics with the aid of SPSS version 20. The results of the study showed that the athletes’ stride frequency in the 100-metre sprint was in the ‘adequate’ category, with 53% of athletes falling into the ‘adequate’ classification and 40% into the ‘good’ classification. Meanwhile, the athletes’ 100-metre running speed fell into the ‘poor’ category, with 73% of athletes classified as ‘poor’ and 27% as ‘very poor’. Based on these results, it can be concluded that the stride frequency of PASI Soppeng Regency athletes is classified as adequate, whilst their 100-metre running speed remains in the poor category. These findings indicate the need for improved training programmes that focus more on developing the athletes’ running speed.